Spaces for literary production in new order Indonesia and beyond - Salam, Aprinus; Zamzuri, Ahmad (Penerbit Universiti Kebangsaan Malaysia, 2023)
This study discusses the production of literature in Indonesia, particularly during and after the New Order regime. Several elements that require consideration in an examination of the conditions and mechanisms of literary production include external elements such as general production tendencies, literary production tendencies, general ideologies, literary ideologies, and aesthetic ideologies, as well as internal elements such as the cultural and linguistic values experienced by human beings (artists/auteurs). At an empirical level, these conditions and mechanisms are set up by how different forces compete with each other. One of these powers was dominant in the structuration process. This power informed the ultimate results of the production process (i.e., the literary work). The material objects discussed in this article were selected randomly as case studies, testing the hypothesis that, although structures of literary production resulted from commercialization efforts, there remained spaces in which authors could resist outside dominance.